Quality regulations and accreditation standards for clinical chemistry in Turkey - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Objective: The purpose of this paper is to review the Current Status of laboratory quality regulations and accreditation standards in Turkey. Design and method: This paper is written based oil file Current regulations, information collected by available websites and congress proceedings, and personal communications. Results: A total of 14 private and one public laboratory have been accredited according to ISO 15 189 voluntarily. The total number of the JCI accredited hospitals is 24. One hospital has been accredited by HQS. A few medical laboratories have been accredited according to ISO 17025, whereas a lot of them have ISO 9001 certification from Turkish Accreditation Agency, TURKAK. There are no comprehensive laboratory standards and/or regulations to maintain a mandatory minimum quality of laboratories. External QC is not mandatory and there is no national proficiency testing program. It is a requirement to get a license. to open a laboratory. There are residency programs for clinical chemistry and clinical microbiology. The Association of Clinical Biochemists, KBUD, is the youngest society in the field of clinical chemistry and is a leader in quality and accreditation activities. KBUDEK is ail external QC program of KBUD. KBUD has organized four national and ail international symposiums oil quality and accreditation in addition to annual congresses and courses. Conclusion: The new standard and regulation should be designed and applied to all laboratories to increase the quality of laboratory service in Turkey. It will be useful if the ISO 15189 standard call be incorporated into the national standards and regulations. (c) 2008 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Quality; Accreditation; Laboratory medicine; Standardization; Education; Training; Harmonization; Patient safety; Regulations; Clinical chemistry